Antioxidant & analgesic activities of leaves of Panlata (Derris trifoliate): In vitro investigation (International Journal of Pharmaceutical and Life Sciences, 2012)
In the present study, the antioxidant and analgesic potential of the ethanolic extract of the leaves of Derris trifoliata was evaluated. The free radical scavenging activity of the crude extract on the stable radical 1, 1-diphenyl-2-picrylhydrazyl (DPPH) was determined by comparing the DPPH inhibitory capacity of the extract. In the quantitative assay, Derris trifoliata extract displayed a free radical scavenging activity in the DPPH assay (IC50 = 19 ?g/ml) which is comparable to that of ascorbic acid (IC50 = 7.80 ?g/ml), a well-known standard antioxidant. The analgesic responses of the given samples of extracts were evaluated using the Tail immersion method. In the analgesic activity test, extract at dose of 200 mg/kg and 400 mg/kg exhibited significant (P